Efficacy of virtual reality assisted guided imagery (VRAGI) in a home setting for pain management in patients with advanced cancer: protocol for a randomised controlled trial. Issue 12 (5th December 2022) - Hartshorn, George; Browning, Matthew; Chalil Madathil, Kapil; Mau, Fredric; Ranganathan, Shyam; Todd, Andrew; Bertrand, Jeff; Maynard, Allison; McAnirlin, Olivia; Sindelar, Kailan; Hernandez, Rosalba; Henry Gomez, Teny
Abstract : Introduction: Patients with advanced cancer often experience high levels of debilitating pain and pain-related psychological distress. Although there is increasing evidence that non-pharmacological interventions are needed to manage their pain, pharmacologic modalities remain the preferred treatment . Guided imagery is a form of focused relaxation that helps create harmony between the mind and body and has been shown to significantly improve cancer pain. Our study presents Virtual Reality Assisted Guided Imagery (VRAGI) as a complementary treatment modality to manage chronic pain in patients with cancer. We will conduct a randomised controlled trial to test its impact on patients with advanced cancer in a home setting. Methods and analysis: We will recruit 80 patients from Prisma Health, a tertiary-level healthcare centre based in Greenville, South Carolina, USA. The prospective 2×2 randomised controlled trial will randomise participants into four groups: (1) VRAGI, (2) laptop-assisted guided imagery, (3) VR (no guided imagery) and (4) laptop (no guided imagery). Patients allocated to VR groups will be trained to use a head-mounted display that immerses them in 3D audio–video content. The non-VR group will use a laptop displaying 2D video content. We will collect measures before and during the 3-week intervention as well as 3 weeks after the intervention ends. Measures will include patient-reported outcomes of pain, anxiety, depression and fatigue in addition to opioid use. The primary objective of the current study is to assess the efficacy of VRAGI on pain in the home setting. The secondary objective is to assess the efficacy of VRAGI on opioid use, anxiety, depression and fatigue. Ethics and dissemination: This study was approved by the Prisma Health Institutional Review Board (#Pro00114598) in November 2021. All participants enrolled in the study will provide written informed consent. Dissemination will be through peer-reviewed publications and conference presentations. Trial registration number: NCT05348174, clinicaltrials.gov.